Small molecule NSAID derivatives for impairing powerhouse in cancer cells. (15th June 2022) - Bajpai, Aman; Deepshikha,; Chhabria, Dimple; Mishra, Tripti; Kirubakaran, Sivapriya; Basu, Sudipta
Graphical abstract: Abstract: Mitochondrion emerged as an important therapeutic target for anti-cancer strategy due to its involvement in cancer progression and development. However, progress of novel small molecules for selective targeting of mitochondria in cancer cells remained a major challenge. To address this, herein, through a concise synthetic strategy, we have synthesized a small molecule library of indomethacin and ibuprofen (non-steroidal anti-inflammatory drugs, NSAIDs) derivatives having triarylphosphonium moiety for mitochondria localization. Two of the library members were identified to induce mitochondrial damage through outer membrane permeabilization (MOMP) followed by generation of reactive oxygen species (ROS) leading to the remarkable MCF7 breast cancer cell death through apoptosis. These novel mitochondria targeted NSAID derivatives could open a new direction in understanding mitochondrial biology towards anti-cancer therapeutics in future.